Modeling and analysis of workpiece stability based on the linear programming method - Qin, Guo-hua; Zhang, Wei-hong (International journal of advanced manufacturing technology, 2007)
After being located on a machine bed, a workpiece will be subject to gravity and cutting forces during the machining operation. In order to keep the locating precision as well as the production safety, it is necessary to maintain the workpiece stability. In this paper, a linear programming method is proposed for stability analysis of the workpiece. Based on the linear approximation of the friction cone, a quantitative criterion is established to verify the workpiece stability in association with the rationality of the clamping sequence, magnitude of clamping forces and clamping placement. This criterion allows designers to plan reasonably the clamping sequence, magnitude of clamping forces as well as clamping placement. Compared with existing methods, the main advantage of this approach lies in that the sophisticated computing of contact forces between fixture elements and the workpiece is avoided. In this work, both friction and frictionless cases can be easily taken into account in stability analysis. Mathematical formulations of the method are given and some numerical tests are finally demonstrated to validate the proposed method.